Treatment decisions and surgery variables are predictors of better physical function after total hip and knee arthroplasty: a retrospective cohort study - Janis Nikkhah; Lukas Schöner; Carlos J. Marques; Christoph M. Pros; Reinhard Busse (Arthroplasty)
Abstract Background Demographic factors are driving the further increase of total hip (THA) and total knee arthroplasty (TKA) volumes in the next decades. This will face the healthcare systems with new challenges. To find ways that optimize the utilization of the limited resources, it is important to understand which factors influence the outcomes at different points along the treatment pathway. Questions/purposes We aimed to identify variables associated with physical function from hospital admission to discharge and at 12 months postsurgery (12 M). This study investigated for patients undergoing THA or TKA: What is the association between patients’ characteristics, surgery variables, and treatment decisions with patient-reported outcomes (PROs) at discharge as well as at 12 M? Patients/methods We conducted a secondary, retrospective cohort analysis using longitudinal data from 6,144 THA and TKA patients who participated in the “PROMoting Quality Trial”. Physical function was assessed via the Hip Disability and Osteoarthritis Outcome (HOOS-PS) and Knee Injury and Osteoarthritis Outcome (KOOS-PS) scores. Stepwise selection and multivariate linear regression models were applied to identify variables associated with physical function at discharge and 12 M. The factors analyzed included surgery variables (surgeon presence, surgeon experience, surgery duration, complication) and treatment decisions (early mobilization, remote monitoring), along with patient characteristics. Results We included 3,375 THA patients and 2,769 TKA patients. Admission HOOS-PS score, sex (being male), and early mobilization were the strongest predictors of better physical function at discharge for patients in the THA group, whereas admission HOOS-PS score, senior staff presence, and remote monitoring (intervention group) were significant predictors of better physical function for the THA patients at 12 M. For the patients in the TKA group, admission KOOS-PS score, early mobilization, and high surgeon experience were the strongest predictors of improved physical function at discharge. The admission KOOS-PS score, surgery duration, and being in the remote monitoring group were the strongest predictors of better physical function at 12 M. Conclusion Early mobilization was significantly associated with better physical function at discharge from the clinic in both procedures, TKA and THA. The preoperative physical function scores and being allocated to the remote monitoring group were the strongest predictors of better physical function at 12 M.